2020
DOI: 10.3390/su12051960
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Decarbonization by a New Energy-Baseline Methodology. Case Study

Abstract: The main target of climate change policies in the majority of industrialized countries is to reduce energy consumption in their facilities, which would reduce the carbon emissions that are generated. Through this idea, energy management plans are developed, energy reduction targets are established, and energy-efficient technologies are applied to achieve high energy savings, which are environmentally compatible. In order to evaluate the impact of their operations and investments, companies promote measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Another study presents the application of an energy characterization method based on the ISO 50001 standard in a dry paper production plant, including combining energy management indicators and life cycle assessment indicators [65]. An alternative for establishing energy baselines for the industrial sector and where the energy consumption of each product was identified was presented in [66]. The presented method was applied to the plastic injection process, and the result was an energy baseline in accordance with the requirements of ISO 50001.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study presents the application of an energy characterization method based on the ISO 50001 standard in a dry paper production plant, including combining energy management indicators and life cycle assessment indicators [65]. An alternative for establishing energy baselines for the industrial sector and where the energy consumption of each product was identified was presented in [66]. The presented method was applied to the plastic injection process, and the result was an energy baseline in accordance with the requirements of ISO 50001.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This standard establishes guidelines for planning, implementing, monitoring, and controlling an organization's energy performance through adopting an EnMS (Fichera et al, 2020). The implementation of the EnMS, under ISO 50001 requirements, contributes to reducing energy consumption and thus achieving commitments to reduce carbon footprint in organizations both at the national and international levels (Castrillón-Mendoza et al, 2020), being an element to strengthen the path towards energy sustainability.…”
Section: Introductionmentioning
confidence: 99%